2011
DOI: 10.1088/0957-4484/23/1/015708
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-assisted growth and selective doping of spinel-like gallium oxide nanocrystals in germano-silicate glasses for infrared broadband light emission

Abstract: The target of taking advantage of the near-infrared light-emission properties of nickel ions in crystals for the design of novel broadband optical amplifiers requires the identification of suitable nanostructured glasses able to embed Ni-doped nanocrystals and to preserve the workability of a glass. Here we show that Ni doping of Li(2)O-Na(2)O-Ga(2)O(3)-GeO(2)-SiO(2) glass (with composition 7.5:2.5:20:35:35 and melting temperature 1480 °C, sensibly lower than in Ge-free silicates) enables the selective embeddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…This trend has been also observed in germanate-based materials for which the authors have shown by optical absorption measurements that Ni ions are fully embedded in the crystalline phase. [ 53 ] No emission in the near-infrared could be obtained in our glass material, even for a 980 nm excitation, as previously reported for several glass systems. [ 48,54,55 ] In the glass ceramic, the emission observed at around 1300 nm for a similar excitation corresponds to octahedral coordinated Ni 2+ ions ( 3 T 2 → 3 A 2 transition).…”
Section: Full Paper Full Paper Full Papersupporting
confidence: 86%
See 1 more Smart Citation
“…This trend has been also observed in germanate-based materials for which the authors have shown by optical absorption measurements that Ni ions are fully embedded in the crystalline phase. [ 53 ] No emission in the near-infrared could be obtained in our glass material, even for a 980 nm excitation, as previously reported for several glass systems. [ 48,54,55 ] In the glass ceramic, the emission observed at around 1300 nm for a similar excitation corresponds to octahedral coordinated Ni 2+ ions ( 3 T 2 → 3 A 2 transition).…”
Section: Full Paper Full Paper Full Papersupporting
confidence: 86%
“…[ 48,54,55 ] In the glass ceramic, the emission observed at around 1300 nm for a similar excitation corresponds to octahedral coordinated Ni 2+ ions ( 3 T 2 → 3 A 2 transition). [53][54][55] The Ni 2+ luminescence emission around 1300 nm in the octahedral site has already been reported. [ 48,54,55 ] In Figure 4 b, the emission maximum is located at 1325 nm.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 81%
“…Particularly, no data are available on the intrinsic properties of g-Ga 2 O 3 NCs in glass, since the only studies on embedded variants were essentially aimed at obtaining convenient hosts for IR-emitting ions, such as Ni 2+ and Cr 4+ . 15,17,34 As a result, the data in Fig. 2 constitute the rst quantitative insight into the absorption edge of g-Ga 2 O 3 as a nanophase in a solid matrix.…”
Section: Resultsmentioning
confidence: 80%
“…Doping the investigated glass with Ni 2+ ions gives rise, in fact, to full incorporation of Ni 2+ into g-Ga 2 O 3 NCs upon nanocrystallization, as we found in a previous work by registering the changes of Ni 2+ crystal eld absorption and IR luminescence. 15 The selective doping of NCs with Ni 2+ ions gives a tool for lowering N A by means of heterovalent cations with oxidation state smaller than Ga 3+ . Bearing in mind that acceptors consist of (V O , V Ga ) 0 complexes -and that the presence of native V Ga is somewhat related to the oxygen deciency determined by the synthesis conditions -we expect that Ni 2+ ions could lower the number of Ga 3+ vacancies required by charge neutrality at a xed oxygen defectiveness.…”
Section: W(r)mentioning
confidence: 99%
See 1 more Smart Citation